Effects of choice of soil constitutive model on seismic performance of moment-resisting frames experiencing foundation rocking subjected to near-field earthquakes. Issue 121 (June 2019) - Yeganeh, Navid; Fatahi, Behzad
Abstract: The current study investigated the extent to which the choice of the soil constitutive models can impact the predicted seismic performance of a 20-story reinforced concrete moment-resisting building with a mat foundation considering the Seismic Soil-Structure Interaction (SSSI). Since the soil, in general, is the weakest material, involved in the commonplace geotechnical engineering projects, a soil constitutive model would be able to rule the dynamic response of the system. In this research, the hardening plasticity-based soil constitutive model, named "hyperbolic hardening with hysteretic damping", in conjunction with the two simple, conventional soil models, namely, the isotropic elastic with hysteretic damping model, and elastic-perfectly plastic Mohr-Coulomb with hysteretic damping model, were invoked in the three-dimensional coupled soil-structure numerical simulations using FLAC3D software. The direct method of analysis was used for analyzing the soil-foundation-structure system in one single step without a need to separately analyze each part of the domain. The cherry-picked earthquake excitations, viz, the 1999 Chi-Chi (Taiwan), and 2011 Kohriyama (Japan), were scaled by means of the widely-used response spectrum matching method as per the design response spectrum of a strong rock. The plastic moment concept was employed so as to assign the elastic-perfectly plastic model to the superstructure and its foundation. Additionally, the strain-compatible shear modulus and damping dependency on the cyclic shear strain were considered via the programmed hysteretic damping algorithm. The numerical predictions included the response spectra at the seismic bedrock and ground surface, base shear forces, shear force distributions along the building height, maximum and permanent foundation displacements, and foundation rocking, plus the flooring lateral deflections and inter-story drifts. The life safety limits for the transient and residual total inter-story drift ratios were not met whilst considering the soil pre-failure plasticity. The concluded remarks herein on the significant effects of the soil hardening plasticity on the seismic performance of the adopted 20-story moment-resisting frame would be applicable to the other structures on a mat foundation, potentially experiencing the foundation rocking amidst the earthquakes. Graphical abstract: Schematic of numerical model concomitant with seismic analysis of soil-foundation-superstructure system, having adopted soil constitutive models, viz, isotropic Elastic with Hysteretic Damping (E-HD), elastic-perfectly plastic Mohr-Coulomb with Hysteretic Damping (MC-HD), and Hyperbolic Hardening with Hysteretic Damping (H2-HD), conducted in FLAC3D, subjected to scaled 1999 Chi-Chi earthquake and scaled 2011 Kohriyama earthquake, so as to investigate effects of soil pre-failure hardening plasticity on seismic performance of 20-story reinforced concrete moment-resisting building frame, supported on mat foundation, experiencing foundation rocking, using soil-structure interaction approach:fx1 Highlights: Hyperbolic hardening with hysteretic damping model was adopted for the Seismic Soil-Structure Interaction (SSSI) analysis. Adopted soil model possessed the shear strain hardening, dilation hardening, and pressure-dependent stiffness. Soil hardening plasticity dislocated the predicted seismic performance level of the adopted 20-story moment-resisting frame. Excluding the soil plasticity would result in the life-threatening seismic design of a building with significant rocking.